Determinants of Korean FDI and Corporate Performance in Latin America and the Caribbean in 2000s : Micro and Macro Data Analysis - Kwon, Kisu; Koh, Taejin (Indian Journal of Finance, 2019)
This paper analyzed what determined the FDI flow of Korean firms and how characteristics of local market in Latin America affected the performance of Korean corporations. The empirical results of this study showed that it supported the existing theoretical hypothesis. The test to reveal FDI determinants using macro data indicated that FDI flow increased with GDP of host country and economic boom in the United States. The distance appeared to hamper FDI flow as expected in the basic gravity model, with political corruption in the host country acting as another barrier to FDI. The micro data analysis showed that the characteristics of the local market generally had a positive impact on corporate performance, even though the impact varied depending on each characteristic. For instance, factors that were positively related to corporate sales are market access, political stability, potential for growth, distribution networks, the facility of contracting and payment, suitability for FDI, suitability for resource development, and the predictability of the local market ; well-developed infrastructure, the facility of contract and payment, and suitability for resource development positively affected corporate profit.